2022
DOI: 10.1186/s13054-022-04023-y
|View full text |Cite
|
Sign up to set email alerts
|

Association between early cumulative fluid balance and successful liberation from invasive ventilation in COVID-19 ARDS patients — insights from the PRoVENT-COVID study: a national, multicenter, observational cohort analysis

Abstract: Background Increasing evidence indicates the potential benefits of restricted fluid management in critically ill patients. Evidence lacks on the optimal fluid management strategy for invasively ventilated COVID-19 patients. We hypothesized that the cumulative fluid balance would affect the successful liberation of invasive ventilation in COVID-19 patients with acute respiratory distress syndrome (ARDS). Methods We analyzed data from the multicente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…There is a logical propensity to prioritize fluid restriction since the pathophysiological mechanism to explain the improvement of hematosis by restricting the fluid input is the reduction of tissue, cellular, interstitial, and alveolar edema caused by the lesion of the alveolar-capillary bed by the inflammatory process 36 , 37 . However, the absence of a clearly defined restrictive fluid management strategy in sepsis 4 , 5 , 9 , 38 in patients with ARDS 33 , 35 , 39 , and now in patients with ARDS caused by SARS-CoV-2 40 , makes it challenging to compare various studies and their findings. This challenge arises from the lack of consensus regarding the specific limits for defining a fluid balance as restrictive and the absence of a universally accepted clinical protocol 34 , 41 .…”
Section: Discussionmentioning
confidence: 99%
“…There is a logical propensity to prioritize fluid restriction since the pathophysiological mechanism to explain the improvement of hematosis by restricting the fluid input is the reduction of tissue, cellular, interstitial, and alveolar edema caused by the lesion of the alveolar-capillary bed by the inflammatory process 36 , 37 . However, the absence of a clearly defined restrictive fluid management strategy in sepsis 4 , 5 , 9 , 38 in patients with ARDS 33 , 35 , 39 , and now in patients with ARDS caused by SARS-CoV-2 40 , makes it challenging to compare various studies and their findings. This challenge arises from the lack of consensus regarding the specific limits for defining a fluid balance as restrictive and the absence of a universally accepted clinical protocol 34 , 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Optimizing volume status and cardiac output may thus improve organ perfusion and provide a protective strategy against kidney damage [2]. In fact, fluid restriction and diuretic drugs are widely used in acute lung injury management, including C-ARDS to prevent further deterioration in lung function [33,34]. Indeed, hypovolemia was a frequent finding in our retrospective cohort, and patients who developed PP-AKI had a significantly lower weight-normalized cumulative fluid balance and a lower CVP before starting their first PP cycle.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent trial including 650 COVID-19 patients with acute respiratory distress syndrome (ARDS) [1], Dr. Ahuja et al reported a linear association between cumulative fluid balance and successful liberation from invasive ventilation in the restricted cubic spline function models. This study is well designed, and the conclusions are clear.…”
Section: To the Editormentioning
confidence: 99%
“…In your journal, we recently showed that a higher cumulative fluid balance has an association with a longer duration of ventilation in patients with acute respiratory distress syndrome (ARDS) due to coronavirus disease 2019 (COVID-19), suggesting that restricted fluid management in these patients may be beneficial [1].…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation